Priming with broccoli extract mitigates salinity stress in tomato through enhanced water and Na+/K+ homeostasis - Albaladejo-Marico, Lorena (Journal of plant physiology, 2025)
Copyright © 2025 The Author(s). Published by Elsevier GmbH.. All rights reserved.